Unified Theory of Relativity - Al-Hasani, Hasan Sadik (Journal of natural sciences, life and applied sciences, 2021)
The general and special theories of relativity cause contradictions in physics. While relative theory provides mathematical valid values, it has limitations in many respects including the relative explanation of the tendency of gravity to (time dilation) and the curvature of light beams on large masses. When studying the special theory of relativity, we will find that it is derived from Lorentz's transformations, which came as a result of the failure of Michelson and Morley experiment. It is not the actual distance that the viewer sees, what Lorentz's transformations express. The relative theory of their result equations is inaccurate in describing distance, time, mass, velocity, and the summation of velocities. Because all these equations depended on Lorentz's transformations. Therefore, we need to find new transformations that will describe the actual distance between the observer, and the moving observer and the event.And that the electron is a particle that is moved by a wave, and it is not itself acts like a wave, this enables us to understand the reason for the behaviour of the electron as a wave in the double-slit experiment. The study relied on scrutinizing the necessary reasons for the existence of special relativity and the origin of its derivation. It was the experiment (Michelson and Morley), whose unexpected results scientists could not explain, which led to the derivation of (Lorentz's) transformations in this unfortunate formula, from which the theory of relativity came. A tool has been devised to illustrate the movement of light. The instrument describes a practical experience of the movement of objects when speed is close to the speed of light.The study found that there is an effect of the carrier medium on the wave that made it possible to explain Michelson and Morley experiment, and that in light of this, new transformations were found that correctly describe the distance, length, time, and velocity. Therefore, new laws were put forward to correct the laws that came with theories of general and special relativity.
Keywords: uniform relativity; wave; gravity; Lorentz transformations; Michelson-Morley experiment; double slit experiment